PROJECT ECOSYSTEM OF SECURITY OF TRANSPORT INFRASTRUCTURE OF UKRAINE AND ITS CLIENTS - Ferdman, Hennadii (European Science, 2025)
The article briefly reviews the project of the transport infrastructure security ecosystem of Ukraine; analyzes the main needs of participants in the transport security ecosystem, the conditions of the environment in which they operate, and trends that wi